The Effect of Diet Control on the Leptin Levels in Diabetic Pregnant Women - KA, Muna; A, Mokhtar; MA, Saad; AA, Ahmed; JB, Akbar (IIUM Medical Journal Malaysia, 2015)
Introduction: Leptin is an adipokine that has strong correlation with the body mass index (BMI). Gestational diabetes mellitus (GDM) is a common medical complication associated with pregnancy. Leptin may lose its correlation with the body mass index (BMI) during diabetes due to hormonal rearrangement. Diet control is the first line management in GDM. Leptin reported to increase in pregnancy and further increases in diabetic patients during GDM screening. There is paucity in the reports concerning Leptin levels in GDM patients on diet control. The present study was aimed to evaluate the changes in maternal leptin in pregnancy complicated by GDM on diet control compared to the normal pregnancy in the 3rd trimesters by comparing the means and to find the correlation of Leptin with the body mass index in both groups. Methods: The study included 2 groups: normal pregnancy (n = 40) and pregnancy with GDM under diet control (n = 60) both groups are at 38-40 weeks of gestation. Leptin concentration in serum was measured in both groups and statistically tested using student t test. The BMI were measured and correlated with the Leptin level in test groups. Results: the results indicated that Leptin will nearly triple in the third trimester (38±30 ng/ml) of pregnancy compared to the standard normal non-pregnant. Leptin level was significantly lower in diabetic women on diet control (28±16 ng/ ml) when compared with the non-diabetics (38±30 ng/ml). The hormone has no correlation with the age of the patients but have a positive correlation with the body mass index before and during pregnancy in both groups. Conclusion: Leptin is increasing in pregnancy as part of the physiological changes. Dieting can decrease Leptin level in diabetics’ pregnant women. Diet can restore the hormonal dysregulation of Leptin. Assessment of Leptin level might be used as an indicator for good diet control during pregnancy.